1988
DOI: 10.1016/s0022-5347(17)42815-1
|View full text |Cite
|
Sign up to set email alerts
|

Xenografted Small Cell Undifferentiated Cancer of Prostate: Possible Common Origin With Prostatic Adenocarcinoma

Abstract: The first xenograft line of small cell undifferentiated carcinoma of the prostate (UCRU-PR-2) has been established and characterized. The donor tumor and the xenograft share the common morphological and ultrastructural features of small cell undifferentiated carcinoma (including neurosecretory granules) but also elaborate epithelial membrane antigen and carcinoembryonic antigen, in addition to neurone-specific enolase. The line expresses a diploid DNA complement. Androgen and estrogen receptors are not express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 7 publications
4
17
0
Order By: Relevance
“…In addition, we showed that the pure neuroendocrine small cell prostatic carcinoma lacked detectable AR. The latter is in accordance with the reported absence of AR in a xenografted small cell neuroendocrine carcinoma line originating from a human prostatic carcinoma (Van Haaften-Day et al 1987).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we showed that the pure neuroendocrine small cell prostatic carcinoma lacked detectable AR. The latter is in accordance with the reported absence of AR in a xenografted small cell neuroendocrine carcinoma line originating from a human prostatic carcinoma (Van Haaften-Day et al 1987).…”
Section: Discussionsupporting
confidence: 92%
“…For example, the patient tumor from which the UCRU-PR2 heterotransplant was derived had a distribution among the three cell cycle phases of 81.6%, 11.4% and 6.9% for the G0/G1-phase, S-phase and G2/M-phase, respectively. The third passage of the UCRU-PR2 also had its cell cycle analyzed and the heterotransplant was nearly identical in cell cycle frequency to the original tumor with a distribution of 83.7%, 10.1% and 6.0% in the G0/G1-phase, S-phase and G2/M-phase, respectively [12]. Similar results were found in a separate study of the same heterotransplant for the second and fourth heterotransplanted passages.…”
Section: Karyotype Dna Content and Cell Cycle Frequencysupporting
confidence: 74%
“…The heterotransplanted tumor, UCRU-PR2, obtained by van Haaften-Day et al [12] had a diploid DNA content similar to the original carcinoma tumor. npg However, starting with the seventh passage, 50% of the heterotransplants developed an aneuploid population in addition to the original diploid population [17].…”
Section: Karyotype Dna Content and Cell Cycle Frequencymentioning
confidence: 84%
See 2 more Smart Citations